Analisis kondisi sosial ekonomi pekerja sektor informal (studi kasus pedagang laki lima yang berada dilingkungan jembatan Gentala Arasy Kota Jambi) - Fitri Maulida; Zamzami Zamzami; Yulmardi Yulmardi (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2021)
The purpose of this study was to analyze the social economic conditions of street vendors around the Gentala Arasy bridge. The sample of this research was 44 respondents's experiments. The variables in this study are age, education level, working hours, and capital. Data collection techniques using questionnaires, documentation, and interviews. Data analysis used is the coefficient of determination test and hypothesis test simultaneously. The results obtained from this study include socio-economic street vendors age, education level, and capital proven to increase, only the working hours variable is not increased. The results of the analysis of the coefficient of determination in this study are all statement items have a valid or significant status because the value of t count > t table with the value of R2 Square (0.348) and the results of the hypothesis test show items that correspond to high reliability with a value (0.270a < 0.05)